PENGARUH RETRIBUSI IZIN MENDIRIKAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN KEEROM - Hutabalian, Roida (CENDERAWASIH CONSTITUTIONAL REVIEW, 2025)
This research is to determine the effect of IMB levies on local revenue in Keerom Regency in terms of Regional Regulation Number 1 of 2015. The method used is a normative juridical approach, namely research on legal principles and legal synchronization used to obtain secondary data and a juridical approach. Empirical research is research that looks at the realities that exist in society in order to obtain primary data. The results of the study reveal that Regional Regulation Number 1 of 2015 concerning Retribution for Building Permits in Keerom Regency has not been able to contribute significantly to PAD because the realization of IMB receipts in Keerom Regency has not been as expected. In terms of quantity, every year the realization of IMB retribution revenue increases and in the last two years it has reached the set target. However, in terms of quality, many buildings were erected but no levy was collected because they did not have an IMB. The acceptance of IMB retribution in Keerom Regency has not been maximized because the Keerom Regency government does not yet have a Regional Regulation on IMB.